Attitudes and Knowledge Perspectives of Administrators Necessary for Fostering the Adoption of Computer Technology in School Systems - Maynard J. Bratlien (Educational Considerations, 1986)
The level of training necessary for administrators to gain personal familiarity with computers will approximate the level of training that is generally received in many of the other specialized tasks of administration.